TRANSFORMACIJA LJUDSKEGA IN KULTURNI SPOMIN V NEKATERIH PROZNIH DELIH MIŠKA KRANJCA: Ob stoletnici rojstva Miška Kranjca (1908–1983) (Filološke pripombe, 2019)
The article Transformation of the popular element and cultural memory in selected prose works of Miško Kranjec, which commemorates the centenary of the writer's birth (1908-1983), is an intertextual analysis of Slovenian folk-song references in Kranjec’s short stories Na valovih Mure (1931) and Lepa Vida prekmurska (1972) as well as in his novels Povest o dobrih ljudeh (1940) and Strici so mi povedali (1974). As such, the article corroborates the idea that the syncretic illustration (text and melody) of the Slovenian folk song is an intertextual source of inspiration not only for individually authored poetry but likewise for the prose of any period and style of the Slovenian literary history.